Sistematic Literature Review (SLR): Desain E-Modul Berbasis Etnomatematika Pada Materi Matriks - Ranita, Ranita; As Elly; Khathibul Umam Zaid Nugroho (AB-JME: Al-Bahjah Journal of Mathematics Education, 2025)
This study aims to identify and systematically analyze ethnomathematics-based E-Module learning on matrix material. The method used in this study is Systematic Literature Review (SLR). Data collection and analysis carried out using the SLR method are formulating research problems, literature search, screening inclusion and exclusion criteria, quality assessment, data collection, analyzing data and describing studies. The use of the SLR method is carried out to review and identify journal articles systematically, each process of which follows predetermined steps. Of the 40 articles used, there were only 5 articles that were relevant to this research and explained the need for ethnomathematics-based E-Module teaching materials on matrix materials that can be used as an effort to know and understand students' ability to understand basic mathematical concepts and be able to implement technology in each learning process. So that the use of ethnomathematics-based E-Modules on matrix material is able to have a positive influence on the learning process of students, because it is able to increase understanding, involvement, and relevance of mathematical concepts to everyday life and student culture.